PENGARUH LATIHAN BRANDT DAROFF TERHADAP VERTIGO SYMPTOM SCALE-SHORT FORM (VSS-SF) PADA PENDERITA VERTIGO - Zuryaty Zuryaty; Mohammad Lutfi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2020)
Vertigo is a sensation where someone or the surrounding object is moving or spinning which is usually accompanied by nausea, vomiting and loss of balance. Vertigo Symptom Scale divided into 3 categories that are mild, moderate, and severe. The number of incidence of vertigo in Poly Nerve, Syarifah Ambami Rato Ebu Hospital In Bangkalan Regency in 2013-2016 is still high. The purpose of this study is to analyze the effect of giving brandt darooff exercise in decreasing vertigoc patients vertigo symptom scale, in Poly Nerve, Syarifah Ambami Rato Ebu Hospital In Bangkalan Regency. The research design was Quasy-Experiment with quantitative approach involved control group. The population in this studied was the patient who was suffered from vertigo in Poly Nerve, Syarifah Ambami Rato Ebu Hospital In Bangkalan Regency as many as 58 respondents; 18 samples were taken by simple random sampling technique, 9 served as the treatment group and 9 as the control group. The result were analyzed by using Paired T-test and independent Test. In the paired t-test analysis indicated that there was differenced of Vertigo Symptom Scale before and after the Brandt Daroff exercise in the treatment group (ρ – value 0,000 < α 0,05), no differenced Vertigo Symptom Scale in the group that were not given the Brandt Daroff exercise in the control group (P-value 0.222 > α 0,05).On independent t-test analysis that compared the treatment group and the control group were obtained p-value 0,000 indicated that there was an effect of given Brandt Daroff exercise in decreasing the Vertigo Symptom Scale. For vertigo sufferers and medical personnel, it is hoped to use Brandt Daroff training for nonpharmacology treatment and as a complementary therapy in in decreasing the Vertigo Symptom Scale.